(untitled) (Experimental biology, 2022)
The intensive industrial and power sectors generate huge amounts of diverse wastes which have detrimental consequences for the environment if not properly managed. Fly ash is one of the most complex and abundant anthropogenic wastes and has traditionally been considered as highly problematic for the treatment and disposal. Being dumped on indigenous and community lands, FA-wastes block their usage and contaminate terrestrial and aquatic ecosystems. These detrimental processes lead to chronic pollution and degradation of waters, soils, and air. Our previous pilot studies implied that the addition of coal-derived substances to soil help to improve soil physicochemical and biological properties stimulating plant growth and enhancing crop yield. The main advantage of FA as compared to many other inorganic amendments is that it can be easily engineeringly optimized due to its precisely characterized chemical composition, a specific combination of surface properties, and hierarchical porosity. The use of beneficial soil microorganisms as well as HA in combination with FA can potentially stimulate crop production through biofertilization mechanisms, including biological nitrogen fixation, phosphate solubilization, phytohormone production, and biocontrol processes. Thus, PGPR is a key factor in maintaining soil fertility as a candidate for FA-HA composite engineering and co-inoculation could be an excellent application. The aim of the proposed research is to develop technology for the production of highly efficient biotechnological fertilizer of new-generation – FA-HA-PGPR. Synthesis of novel fertilizers by a combination of FA with traditionally used farmyard manure, digestate, compost, and sludge has a very promising potential. However, the ecological and biogeological behavior of FA is not yet adequately studied. Engineering of quality FA-based products requires determination of the nutrient release characteristics and detailed examination of its performance for various soil types and agroecological conditions. As a result, FA-HA-PGPR will be engineered and functionalized as a new fertilizer.